Tatalaksana bedah pada eksotropia traumatika et causa ruptur total otot rectus medial: laporan kasus - Christine Natalia Gunawan; Ni Made Ayu Surasmiati; I Made Agus Kusumadjaja; Ni Made Laksmi Utari (DiscoverSys Inc., 2021)
Introduction: Traumatic strabismus may result because of closed or open head and/or orbital trauma. Trauma to the extraocular muscles will often result directly in specific ocular motility disorders. Vertical transposition is one of the surgical management in traumatic exotropia with medial rectus muscle total rupture. The aims of case report are to know about examination and management in patient with traumatic exotropia.Case Illustration: Male, 30 years old, came with chief complaints pain on the right eye after being exposed a wire bounce when take off a banner wire, with squint eye, blurry vision, diplopia, redness, bleeding. On ophthalmology examination, 45° exotropia, visual acuity on the right eye 6/18 ph NI, proptosis, edema, hematom, spasm palpebral. Medial rectus muscle rupture, full thickness conjunctival rupture, cresent shaped, 15x7mm, 3 mm from limbal. Eyeball movement limited to medial, superomedial, inferomedial, FGT medial parese right eye (RE). visual acuity on the left eye 6/6, anterior and posterior segment within normal limit. Patient was diagnosed with traumatica exotropia et causa medial rectus muscle total rupture right eye (RE) with complication axial proptosis ec retrobulbar hemorrhage, palpebral hematom, full thickness conjunctival ruptured, sub conjunctival bleeding, erosion cornea, iridoplegy, traumatic iritis. Vertical transposition with augmented Hummelsheim technique, cantotomy cantolysis, repair conjunctival ruptured was done to the patient. Conclusion: Vertical transposition is one of the surgical management in traumatic exotropia caused by medial rectus muscle total rupture Pendahuluan: Eksotropia traumatik dapat disebabkan oleh adanya trauma terbuka/tertutup pada kepala/mata. Trauma pada otot ekstraokuler akan menyebabkan gangguan gerakan bola mata yang spesifik. Salah satu penanganan bedah pada eksotropia traumatik karena ruptur total otot rektus medial adalah dengan transposisi vertikal. Tujuan dari pembuatan laporan kasus in adalah untuk mengetahui pemeriksaan dan penanganan pasien dengan eksotropia traumatika.Laporan kasus: Pria dengan usia 30 tahun, datang dengan keluhan nyeri pada mata kanan setelah terkena pentalan kawat, disertai mata juling keluar, pandangan ganda, kabur, berdarah, mata merah. Pada pemeriksaan oftalmologi didapatkan eksotropia 45°, tajam penglihatan mata kanan 6/18 ph NI, dengan proptosis, edema, hematom, spasme pada palpebra. Pada konjungtiva didapatkan tampak ruptur rektus medialis, ruptur konjungtiva full thickness bentuk bulan sabit ukuran 15x7mm, 3 mm dari limbus. Gerakan bola mata terhambat ke medial, superomedial, inferomedial, Forced Generation Test (FGT) mata kanan paresis ke medial. Tajam penglihatan mata kiri 6/6, segmen anterior dan posterior dalam batas normal. Pasien didiagnosis dengan eksotropia traumatika et causa ruptur total otot rektus medial oculi dextra (OD) dengan komplikasi proptosis axial ec suspek pendarahan retrobulbar, hematom palpebral, ruptur konjungtiva full thickness, pendarahan sub konjungtiva, erosi kornea, iridoplegia, traumatic iritis. Pada pasien ini dilakukan transposisi vertikal dengan teknik augmented Hummelsheim, kantotomi kantolisis, dan repair ruptur konjungtiva full thickness. Simpulan: Transposisi otot rektus vertikal merupakan salah satu tindakan untuk tatalaksana pembedahan pada eksotropia traumatika et causa ruptur total otot rektus medial